Exploring Piper betle L. and Psidium guajava L.: Natural Remedies for Enhancing Oral Health - Fathilah AR; Wan Ismail WN; Yusoff M; Rahim ZHA (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
The study aimed to identify novel plant extract agents for controlling dental plaque, focusing on inhibiting the initial adherence of early plaque-forming bacteria to the tooth surface. Streptococcus sanguinis, Streptococcus mitis, and Actinomyces sp., key bacteria in early plaque formation, were tested. Aqueous extracts of Piper betle and Psidium guajava demonstrated antimicrobial activity with MIC values ranging from 2.61 to 4.69 mg/mL while exhibiting safe toxicity levels (LC50 and EC50). Additionally, both extracts contained 9.25 and 11.5 ppm fluoride, respectively. Psidium guajava extract also showed aggregating activity. Furthermore, both extracts reduced bacterial cell-surface hydrophobicity, potentially limiting bacterial adhesion to tooth surfaces during plaque development. Scanning electron microscopy (SEM) images supported these findings, indicating a bacteriostatic effect where bacterial growth and division were hindered. Overall, Piper betle and Psidium guajava extract exhibit promising antiplaque activities by preventing bacterial adhesion and growth, highlighting their potential in oral health maintenance.